Endometriosis and New-Onset Coronary Artery Disease in Taiwan: A Nationwide Population-Based Study - Wei, Chun-Hui; Chang, Renin; Wan, Yu Hsun; Hung, Yao-Min; Wei, James Cheng-Chung (Frontiers in Medicine, 2021)
Endometriosis (EM) with chronic inflammation may accelerate the progression of atherosclerosis. Currently, no large or randomized clinical studies have assessed the incidence of cardiovascular events in patients with endometriosis in Asia to investigate whether incident EM is associated with a higher risk of new-onset coronary artery disease (CAD). In this study of a nationwide cohort in Taiwan, we identified 13,988 patients with newly diagnosed EM from 1 January, 2000, through 31 December, 2012. EM and non-EM groups were matched by propensity score at a ratio of 1:1. Of a total 27,976 participants, 358 developed CAD. The incidence rate in the EM group was higher than that in the non-EM group (1.8 per 1,000 person-years vs. 1.3 per 1,000 person-years) during the follow-up period. The adjusted hazard ratio (aHR) of CAD for the EM group was 1.52 with a 95% confidence interval (1.23–1.87, p < 0.001) after adjusting for demographic characteristics, comorbidities, surgical procedures, frequency of outpatient visits, and medications. Stratified analysis revealed that, among four age groups (20–39, 40–49, 50–54, and above 55 years), the 20–39 years sub-group was associated with a higher risk of CAD (aHR, 1.73; 95% CI, 1.16–2.59, p = 0.008). Several sensitivity analyses were conducted for cross-validation, and it showed consistent positive findings. In conclusion, this cohort study revealed that patients with symptomatic EM in Taiwan were associated with increased risk of subsequent CAD than patients without medical records of EM. Further prospective studies are needed to confirm this causal relationship.